PENDAMPINGAN PETANI MELALUI PEMBELAJARAN PEMBERDAYAAN MASYARAKAT UNTUK PENINGKATAN PRODUKTIVITAS KAKAO DI KABUPATEN BANTAENG - Asman, .; Rosmana, Ade; Zainal, . (Departemen Budidaya Pertanian Fakultas Pertanian UNHAS, 2020)
In recent years, cocoa productivity in South Sulawesi has tended to decline, resulting in many farmers turning to other jobs and planting other commodities whose economic value is no better than cocoa. Various cocoa development programs have been launched, but significant improvements than expected productivity have not yet occurred. Bantaeng Regency has great potential in developing cocoa plants. Although positive results have been obtained for some cocoa farmers, the target of 2000 kg / ha has not been achieved. Various problems have been able to be mapped both at the on-farm level and at the off-farm level. The introduction of cocoa management technology and empowerment of farmers is an important key in increasing cocoa production, involving all stakeholders including universities will be an important and sustainable solution for the sustainability of people's cocoa. In addition, the government has the desire to develop organic cocoa. To support the achievement of productivity targets and organic cocoa, the improvement of the production system using non-chemical fertilizers and pesticides will be carried out in collaboration with the Faculty of Agriculture, Hasanuddin University. This activity will focus on good plantation practices, rejuvenation of planting and nursery management, manufacture of fertilizer from plant materials, composition of plant materials, and formulation of plant materials, multiplication of disease control microorganisms, mixing of microorganisms with composted plant material, and post-harvest management. This program has distributed cocoa plantation management technology and improved skills and knowledge to cocoa farmers, especially to students, farmers and farmer groups who were very satisfied with the arrival of KKN PPM DIKTI students who accompanied them to improve their gardens, activities and assistance materials were carried out well and Successful, students are very happy with this activity because of their increased knowledge and skills. Keywords: Community services, Empowerment, Cacao Farmers, University students.ABSTRAK Dalam beberapa tahun belakangan, produktivitas kakao di Sulawesi Selatan cenderung menurun mengakibatkan banyak petani beralih ke pekerjaan lain dan menanam komoditi lain yang nilai ekonominya tidak lebih baik dari kakao. Berbagai program pengembangan kakao telah banyak diluncurkan, namun peningkatan signifikan daripada produktivitas yang diharapkan belum juga terjadi. Kabupaten Bantaeng memiliki potensi yang besar dalam pengembangan tanaman kakao. Walau hasil positif telah diperoleh bagi sebagian petani kakao, namun target 2000 kg/ha belum dicapai. Berbagai persoalan telah mampu dipetakan baik pada tingkat on-farm maupun pada tingkat off-farm. Introduksi teknologi pengelolaan kakao dan pemberdayaan petani menjadi kunci penting dalam peningkatan produksi kakao, pelibatan semua stakeholder termasuk universitas akan menjadi solusi penting dan berkelanjutan bagi kelangsungan perkakaoan rakyat. Selain itu pemerintah mempunyai keinginan untuk mengembangkan kakao organik. Untuk mendukung pencapaian target produktivitas dan kakao organik, maka perbaikan sistem produksi dengan penggunaan pupuk dan pestisida non kimia akan dilakukan dengan kerjasama Fakultas Pertanian, Universitas Hasanuddin. Kegiatan ini akan difokuskan pada praktek perkebunan yang baik, peremajaan tanam dan manajemen pembibitan, pembuatan pupuk dari bahan tanaman, komposisi bahan tanaman, dan formulasi bahan tanaman, perbanyakan mikroorganisme pengendali penyakit, pencampuran mikroorganisme dengan bahan tanaman yang dikomposkan, dan pengelolaan pasca panen. Program ini telah melakukan distribusi teknologi manajemen kebun kakao dan meningkatkan keterampilan dan pengetahuan kepada petani kakao, terkhusus kepada mahasiswa, Petani dan Kelompok Tani sangat puas dengan kedatangan Mahasiswa KKN-PPM DIKTI yang mendampingi mereka memperbaiki kebun mereka, Kegiatan dan materi Pendampingan terlaksana dengan baik dan berhasil, Mahasiswa sangat senang dengan kegiatan ini karena bertambahnya pengetahuan dan keterampilan mereka.Kata kunci: Pengabdian masyarakat, Pemberdayaan, Petani Kakao, Mahasiswa.